2023
DOI: 10.2196/48754
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Artificial Intelligence for Detecting Anxiety: Systematic Review and Meta-Analysis

Alaa Abd-alrazaq,
Rawan AlSaad,
Manale Harfouche
et al.

Abstract: Background Anxiety disorders rank among the most prevalent mental disorders worldwide. Anxiety symptoms are typically evaluated using self-assessment surveys or interview-based assessment methods conducted by clinicians, which can be subjective, time-consuming, and challenging to repeat. Therefore, there is an increasing demand for using technologies capable of providing objective and early detection of anxiety. Wearable artificial intelligence (AI), the combination of AI technology and wearable de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 66 publications
2
4
0
Order By: Relevance
“…To elaborate, although the pooled mean in this review was 85.6%, the average accuracy estimates in the previous reviews were 87.6% (50%-100%) [ 28 ], 87% (70.8%-99%) [ 34 ], 86% (60%-100%) [ 15 ], 85.4% (64.5%-98.3%) [ 35 ], 84.2% (51.2%-100%) [ 24 ], and 82.9% (53%-99%) [ 13 ]. Furthermore, this review showed findings comparable with those of previous studies on the performance of wearable AI in detecting depression [ 74 ] and anxiety [ 75 ]. Specifically, the pooled mean accuracies of wearable AI in detecting depression and anxiety were 89% [ 74 ] and 82% [ 75 ], respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To elaborate, although the pooled mean in this review was 85.6%, the average accuracy estimates in the previous reviews were 87.6% (50%-100%) [ 28 ], 87% (70.8%-99%) [ 34 ], 86% (60%-100%) [ 15 ], 85.4% (64.5%-98.3%) [ 35 ], 84.2% (51.2%-100%) [ 24 ], and 82.9% (53%-99%) [ 13 ]. Furthermore, this review showed findings comparable with those of previous studies on the performance of wearable AI in detecting depression [ 74 ] and anxiety [ 75 ]. Specifically, the pooled mean accuracies of wearable AI in detecting depression and anxiety were 89% [ 74 ] and 82% [ 75 ], respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, this review showed findings comparable with those of previous studies on the performance of wearable AI in detecting depression [ 74 ] and anxiety [ 75 ]. Specifically, the pooled mean accuracies of wearable AI in detecting depression and anxiety were 89% [ 74 ] and 82% [ 75 ], respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Apart from physical illnesses, wearables have been integrated into managing mental health conditions such as anxiety. Wearables have become a popular tool for automatically, objectively, and more effectively predicting and detecting anxiety disorders [48]. According to the American Psychiatric Association (APA) [49] and the Global Burden of Disease (GBD) [50], anxiety disorders are among the most common mental illnesses in the world, with 4% of the world population suffering from the condition.…”
Section: Wearables For Health and Well-being Managementmentioning
confidence: 99%
“…According to the American Psychiatric Association (APA) [49] and the Global Burden of Disease (GBD) [50], anxiety disorders are among the most common mental illnesses in the world, with 4% of the world population suffering from the condition. Usually, physicians use self-assessment questionnaires or interview-based evaluation techniques to measure anxiety symptoms [48]. These procedures can be subjective, time-consuming, and difficult to replicate.…”
Section: Wearables For Health and Well-being Managementmentioning
confidence: 99%
See 1 more Smart Citation